2010
DOI: 10.1186/1471-2180-10-270
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D promotes Arcanobacterium haemolyticum adhesion via lipid raft remodeling and host cell death following bacterial invasion

Abstract: BackgroundArcanobacterium haemolyticum is an emerging bacterial pathogen, causing pharyngitis and more invasive infections. This organism expresses an unusual phospholipase D (PLD), which we propose promotes bacterial pathogenesis through its action on host cell membranes. The pld gene is found on a genomic region of reduced %G + C, suggesting recent horizontal acquisition.ResultsRecombinant PLD rearranged HeLa cell lipid rafts in a dose-dependent manner and this was inhibited by cholesterol sequestration. PLD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 52 publications
0
53
0
1
Order By: Relevance
“…The effect of hemolysins on the association of bacteria with cells was unexpected, but a directed search of the literature showed that the phenomenon is not unprecedented (62)(63)(64)(65). Our findings add important new information by showing (i) that hemolysins increase the association of Gram-positive or Gram-negative bacteria with mammalian cells, (ii) that the effect does not depend on chemotaxis, (iii) that it is independent of pili, and (iv) that it depends on an active response of target cells, which is apparently under the control of class III PI3Ks.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of hemolysins on the association of bacteria with cells was unexpected, but a directed search of the literature showed that the phenomenon is not unprecedented (62)(63)(64)(65). Our findings add important new information by showing (i) that hemolysins increase the association of Gram-positive or Gram-negative bacteria with mammalian cells, (ii) that the effect does not depend on chemotaxis, (iii) that it is independent of pili, and (iv) that it depends on an active response of target cells, which is apparently under the control of class III PI3Ks.…”
Section: Discussionmentioning
confidence: 99%
“…Lucas et al (2010) showed that phospholipase D reorganized lipid rafts, resulting in the clustering of adhesion receptors on host cells; thus, it could play a critical role in bacterial adhesion. Furthermore, phospholipase D-expressing A. haemolyticum was able to escape from vacuoles, and phospholipase D caused cellular necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…upon Gram staining and weak haemolytic activity on conventional media (García-de-la-Fuente et al, 2008). It is therefore important to assess the bacteriological characteristics and presence of virulence factors, such as phospholipase, to identify A. haemolyticum (Lucas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…4) (55). This type of SMase D lacks the HKD motif seen in phospholipase Ds (PLDs), explaining why they do not act on phosphatidylcholine (PC) and other glycerophospholipids, although sometimes they are mistakenly referred to as PLDs (56)(57)(58). Their catalytic site, identifiable by the position of the Mg 2ϩ ion, which is essential for activity and octahedrally coordinated by strictly conserved residues, is made up of hydrophobic loops and a negatively charged surface (55).…”
Section: Sphingomyelinase Ds Which Adopt a Tim Barrel Structurementioning
confidence: 99%
“…haemolyticum, which causes pharyngitis and several invasive diseases, including septic arthritis, osteomyelitis, and meningitis, produces a SMase D which likely plays a role in pathogenicity (57). A wild-type A. haemolyticum strain escapes the phagosome and causes host cell death, apparently by necrosis, whereas a mutant strain lacking the SMase D-encoding gene has a defective phagosomal escape capacity, indicating that SMase D is involved in phagosomal membrane disruption (57). The chromosomal genome of the emergent pathogen C. ulcerans, which causes among other diseases pharyngeal and pulmonary infections in humans, includes a homologous SMase D among its repertoire of virulence factors (63).…”
Section: Sphingomyelinase Ds Which Adopt a Tim Barrel Structurementioning
confidence: 99%